Survival and complications of cytoreductive surgery with hyperthermic intraperitoneal chemotherapy in patients with intra-abdominal malignancies: A meta-analysis of randomized controlled trials - Jian, Changchun; Mou, Hai; Zhang, Ye; Fan, Qingxin; Ou, Yunsheng (Frontiers in Pharmacology, 2023)
Background: In recent years, hyperthermic intraperitoneal chemotherapy (HIPEC) combined with cytoreductive surgery (CRS) has been utilized as an active treatment in the prevention and treatment of peritoneal metastasis, with controversial results. This study sought to determine the impact of HIPEC+CRS on patient survival and adverse events (AEs) by reviewing randomized controlled trials (RCTs) for all types of intra-abdominal malignancies. Methods: A PubMed, Embase, Cochrane Library, Web of Science and Clinical Trials.gov search extracted all RCTs studies until October 12, 2022, examining the CRS+HIPEC vs. CRS alone strategies in the treatment of various types of intra-abdominal malignancies. The outcomes included overall survival (OS), disease-free survival (DFS), relapse-free survival (RFS), progression-free survival (PFS) and AEs. The dichotomous data were pooled and reported as odds ratios (ORs) with 95% confidence intervals (CIs). The survival outcome data were pooled using hazard ratios (HRs) and corresponding 95% CIs. The Cochrane Collaboration's Risk of Bias Tool was used to assess the risk of bias in the included studies. Results: Our analysis showed no different OS between the CRS+HIPEC and CRS alone groups (HRs: 0.79, 95% CI 0.62-1.01). Subgroup analysis showed that CRS+HIPEC improved the OS of gastric cancer patients (HRs: 0.49, 95% CI 0.32-0.76) compared with CRS alone. However, CRS+HIPEC did not significantly improve the OS of colorectal cancer (HRs: 1.06, 95% CI 0.81-1.38) and ovarian cancer (HRs: 0.82, 95% CI 0.62-1.07) patients. In addition, there was no significant difference in DFS/RFS (HR: 0.78, 95% CI 0.57-1.07) or PFS (HR: 1.03, 95% CI 0.77-1.38) between the two groups. Compared with CRS alone, CRS with HIPEC had greater nephrotoxicity (OR: 0.45, 95% CI 0.21-0.98), while other AEs did not differ significantly between the two groups. Conclusions: Our results suggest that CRS+HIPEC may improve OS in gastric cancer patients compared with CRS alone, but we did not observe a benefit for DFS/RFS. For patients with ovarian and colorectal cancer, our results suggest that HIPEC+CRS does not appear to improve survival outcomes. In addition, CRS+HIPEC has higher nephrotoxicity than CRS alone. More evidence from RCTs is needed to evaluate whether the use of CRS+HIPEC is an appropriate option.